RELATIONSHIP BETWEEN UPPER RESPIRATORY TRACT SYMPTOMS AND TREATMENT SEEKING BEHAVIOUR IN HEALTHY ATTENDANTS OF PATIENTS PRESENTING TO OPD CLINICS OF BBS TEACHING HOSPITAL ABBOTTABAD - Abbasi, Munir Ahmad; Muhammad Nawaz,; Adeel Alam, (Journal of Ayub Medical College Abbottabad, 2024)
Background: Indiscriminate use of antibiotics is a well-known reason for increasing antimicrobial resistance. Upper respiratory tract infection presents with similar symptoms and signs irrespective of its bacterial or viral causes and is either ignored or managed aggressively by the primary care physicians. The objective was to determine the relationship between upper respiratory tract infections and treatment-seeking behaviour in healthy individuals attending the OPD clinics of BBS Teaching Hospital with their sick family members. Methods: Six hundred and eighty-five healthy individuals who accompanied patients to the OPD clinics of BBS Teaching Hospital, Abbottabad were enrolled in this cross-sectional survey. They were given a modified questionnaire to respond to and their replies were analyzed for assessment. Results: In a survey of 685 individuals, 98.2% were aware of antibiotics, but only 28.6% correctly understood their use against infections. Misconceptions about antibiotic resistance were common, with 54.5% believing it arises from human immunity. Only 31.53% consulted a doctor for upper respiratory symptoms and 72.6% of those expected antibiotics. Women showed higher antibiotic knowledge than men, but education level was a stronger predictor of both knowledge and attitudes. Conclusion: This study highlights a critical gap in public understanding and responsible usage of antibiotics, particularly in the context of upper respiratory tract infections. This study reveals that increased awareness and more informed attitudes about antibiotic resistance correlate with a decreased likelihood of inappropriate antibiotic prescription.